Consultative Leadership and Ethical Governance in Non-Formal Islamic Education: A Case Study of Musyawarah Practice - Inayati, Evi Sovia; Faiza, Gilang Rakha; Dewi, Wahyuningsih Saputri (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study explores the leadership style and decision-making process at Madrasah Diniyah Al Munajah, focusing on how musyawarah (consultative deliberation) is practiced under the leadership of Principal A. It addresses the gap in empirical research on Islamic educational leadership by examining how ethical and inclusive leadership can sustain institutional resilience in a community-based madrasah. The study argues that culturally rooted leadership, grounded in collaboration and moral responsibility, is key to overcoming challenges in non-formal educational settings. Design/methods – A qualitative case study design was adopted, with data collected through semi-structured interviews, document analysis, and field observations. Thematic analysis was used to identify patterns related to leadership behavior, decision-making strategies, financial management, and stakeholder engagement. The study employed manual coding, analytical memos, and member checking to ensure the validity and reliability of the results. Findings – The study found that Principal A’s leadership emphasized inclusive participation in institutional decision-making, empathetic financial practices, and constructive responses to organizational challenges. Collaborative governance helped sustain the madrasah through transparent tuition policies, external donor engagement, and mutual trust between staff and stakeholders. Despite institutional limitations and policy-induced challenges, ethical leadership anchored in musyawarah promoted adaptability and commitment to the madrasah’s mission. Research implications/limitations – The findings are limited by the single-case design focused on one leader and institution, which restricts generalizability. The context-specific nature of the case suggests that broader applicability requires caution. Practical implications – The study offers a model for educational leaders in religious or community-based schools facing resource constraints and policy transitions. It underscores the importance of integrating spiritual ethics, participatory governance, and community collaboration into leadership development frameworks. Originality/value – This research contributes original empirical insight into Islamic educational leadership, showing how musyawarah-based governance sustains institutional integrity and relevance. It invites further research on similar leadership models across diverse cultural and educational environments.